Legal Protection For Customers Against ITE Crimes (Electronic Information And Transactions ) On Digital Bank Services - Astanti, Dhian Indah; S, Amri Panahatan; Heryanti, B Rini (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Since the legal relationship between consumers and banks is one built on trust, legal protection for customers is crucial given that banks are financial entities whose operation cannot be divorced from the role of customers. The usage of technology is a crucial component of practically all non-negotiable communal activities. In this global age, discussing cybercrime is inextricably linked to discussing computer network security or internet-based information security, particularly when discussing the topic of information as a commodity. Determining client legal protection and bank accountability against ITE crimes in digital banking services is the goal of this research. This study employs a statutory approach and a normative juridical research type. The research will be analytical and descriptive in nature, using secondary data obtained through library research and analytical descriptive research criteria. The research's data is organized logically and methodically, examined using techniques for qualitative analysis, and then presented in a qualitative fashion. According to research findings, efforts are currently being made to develop an independent and effective supervisory system that is always focused and in line with the principles of good governance, effective bank supervision, banking management information systems, intermediation functions, handling problem loans, and implementing risk management. The Indonesian banking industry is currently undergoing a process of restructuring. and the potential for national banks to use anti-money laundering measures and best practices.